Linking cyber and physical spaces through community detection and clustering in social media feeds. (September 2015) - Croitoru, Arie; Wayant, N.; Crooks, A.; Radzikowski, J.; Stefanidis, A.
Highlights: Our analysis includes two major events as captured in Twitter. The themes in cyber and physical communities tend to converge over time. Messages among physical space users are more consistent at the onset of the event. Geolocated users are consuming information more than they produce. Abstract: Over the last decade we have witnessed a significant growth in the use of social media. Interactions within their context lead to the establishment of groups that function at the intersection of the physical and cyber spaces, and as such represent hybrid communities. Gaining a better understanding of how information flows in these hybrid communities is a substantial scientific challenge with significant implications on our ability to better harness crowd-contributed content. This paper addresses this challenge by studying how information propagates and evolves over time at the intersection of the physical and cyber spaces. By analyzing the spatial footprint, social network structure, and content in both physical and cyber spaces we advance our understanding of the information propagation mechanisms in social media. The utility of this approach is demonstrated in two real-world case studies, the first reflecting a planned event (the Occupy Wall Street – OWS – movement's Day of Action in November 2011), and the second reflecting an unexpected disaster (the Boston Marathon bombing in April 2013). Our findings highlight the intricate nature of the propagation and evolution of information both within and across cyber and physical spaces, as well as the role of hybrid networks in the exchange of information between these spaces.